Regulation of proneural gene expression and cell fate during neuroblast segregation in the Drosophila embryo. - Skeath, J.B.; Carroll, S.B. (Development, 1992)
The Drosophila embryonic central nervous system develops from sets of progenitor neuroblasts which segregate from the neuroectoderm during early embryogenesis. Cells within this region can follow either the neural or epidermal developmental pathway, a decision guided by two opposing classes of genes. The proneural genes, including the members of the achaete-scute complex (AS-C), promote neurogenesis, while the neurogenic genes prevent neurogenesis and facilitate epidermal development. To understand the role that proneural gene expression and regulation play in the choice between neurogenesis and epidermogenesis, we examined the temporal and spatial expression pattern of the achaete (ac) regulatory protein in normal and neurogenic mutant embryos. The ac protein is first expressed in a repeating pattern of four ectodermal cell clusters per hemisegment. Even though 5-7 cells initially express ac in each cluster, only one, the neuroblast, continues to express ac. The repression of ac in the remaining cells of the cluster requires zygotic neurogenic gene function. In embryos lacking any one of five genes, the restriction of ac expression to single cells does not occur; instead, all cells of each cluster continue to express ac, enlarge, delaminate and become neuroblasts. It appears that one key function of the neurogenic genes is to silence proneural gene expression within the nonsegregating cells of the initial ectodermal clusters, thereby permitting epidermal development.